2022
DOI: 10.15252/embr.202255502
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of in vitro expanded hematopoietic stem cells

Abstract: This is a repository copy of Identification and characterization of in vitro expanded hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…( 2), unrealistic small estimated values of may be possible because the very small returns a fraction of P-P differentiation as some magnitude. In fact, our group showed that, when the fraction of CD201 + CD150 + KSL population was even around 10%, the post-transplantation chimerism in peripheral blood became almost 0 21 , implying P-P divisions are still possible at least for 10% of the fraction and supporting our assumption on usage of the discretized beta function. 1.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…( 2), unrealistic small estimated values of may be possible because the very small returns a fraction of P-P differentiation as some magnitude. In fact, our group showed that, when the fraction of CD201 + CD150 + KSL population was even around 10%, the post-transplantation chimerism in peripheral blood became almost 0 21 , implying P-P divisions are still possible at least for 10% of the fraction and supporting our assumption on usage of the discretized beta function. 1.…”
Section: Discussionsupporting
confidence: 74%
“…Endothelial Protein C Receptor (EPCR, also known as CD201) exclusively enriches functional HSCs quanti ed by ex vivo and in vivo reconstitution assays 20,21 . We performed single-cell expansion by sorting CD34 −/low CD150 + c-Kit + Sca-1 + lineage marker negative (CD34 − CD150 + KSL) cell populations that are highly enriched in functional HSCs 22,23,24 from mice (Fig.…”
Section: Age-related Bimodal Changes In Functional Hsc Proportionsmentioning
confidence: 99%
“…Cultured HSCs cannot be identified by the same panel of surface markers as freshly isolated HSCs. Endothelial Protein C Receptor (EPCR, also known as CD201) exclusively enriches for functional HSCs, as quantified by e x vivo and in vivo reconstitution assays [ 20 , 26 , 27 ]. The marker, with CD150, has also been recently shown to enrich for cells that possess long-term expansion potential and retain a transcriptional phenotype associated with HSCs after PVA-based culture.…”
Section: Resultsmentioning
confidence: 99%
“…Although is it known that long-term hematopoietic reconstitution is possible from CD150-cells in the E14.5 FL (Kent et al, 2009; Kim et al, 2006; Papathanasiou et al, 2009), how much of the LT-RU biomass they represent is not known. This is an important issue that requires resolution because of how ubiquitously CD150 expression is used as a hurdle criterion for the quantitative and qualitative analysis of the fetal LT-RU pool (for examples see (Che et al, 2022; Ganuza et al, 2022; Gao et al, 2022; Hall et al, 2022; Lee et al, 2022; Patel et al, 2022; Sakai et al, 2022; Van Deren et al, 2022; Young et al, 2021)).…”
Section: Introductionmentioning
confidence: 99%